PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR MENGGUNAKAN MODEL PICTURE AND PICTURE BERBANTUAN MEDIA ULAR TANGGA PADA SISWA KELAS IV SD - Andriani, Wiwin; W, Heny Kusuma; Karjanto, Singgih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of the research is to determine the improvement in learning outcomes in Mathematics for class IV students at SDN 02 Mojorejo, Madiun City through the picture and picture model with the help of snakes and ladders media. This type of research is Classroom Action Research (PTK). The research subjects were 26 students. Research (PTK) was carried out in two cycles, namely cycle I and cycle II. The procedures in this research are planning, implementation, observation and reflection. The data collection techniques are using observation techniques and test techniques. Meanwhile, for data analysis, qualitative data analysis is used, namely by collecting data, reducing data, presenting data, and drawing conclusions as well as quantitative analysis by analyzing data through test results, and measuring the percentage of completeness of test results. The research results after using the Picture and Picture model, learning outcomes in cycle I obtained an average of 88 with a percentage of 62% and in cycle II obtained an average of 90 with a percentage of 92%. The application of the picture and picture model to student learning outcomes has increased by 39% from before the use of this model, so the research results show that the application of the picture and picture model assisted by snakes and ladders media can improve mathematics learning outcomes at SDN 02 Mojorejo, Madiun City.